Expression of scavenger receptors CD163, CD204, and CD206 on macrophages in patients with pulmonary tuberculosis - E. G. Churina; A. V. Popova; O. I. Urazova; M. R. Patysheva; Ju. V. Kolobovnikova; S. P. Chumakova (Бюллетень сибирской медицины)
The aim of the study was to evaluate the expression of scavenger receptors (CD163, CD204, CD206) on macrophages in patients with pulmonary tuberculosis, depending on the clinical form of the disease and sensitivity of the pathogen to anti-tuberculosis drugs.Materials and methods. 64 patients with pulmonary tuberculosis (TB) were examined: 26 patients with disseminated pulmonary tuberculosis (DTB) and 38 patients with infiltrative pulmonary tuberculosis (ITB). Of these, 42 patients secreted Mycobacterium tuberculosis (MBT) sensitive to basic antituberculosis drugs (ATBD), and 22 patients secreted MBT resistant to first-line anti-TB drugs. Material for the study was venous blood. To isolate monocytes from the whole blood in order to transform them into macrophages, Ficoll density gradient centrifugation with a density of 1.077 g / cm3 was used followed by immunomagnetic separation of CD14+ cells. Monocytes were cultured in the X-VIVO 10 medium with gentamicin and phenol red with the addition of macrophage colony-stimulating factor (M-CSF) (5 ng / ml) at a concentration of 1×106 cells / ml with stimulators: interleukin (IL)-4 (10 ng / ml) and interferon (IFN) γ (100 ng / ml). Immunophenotyping of macrophages was performed using monoclonal antibodies to CD163, CD204, and CD206 on the Beckman Coulter CytoFLEX LX Flow Cytometer. The analysis of the obtained data was carried out using the CytExpert 2.0 software. The results were analyzed using statistical methods.Results. Switching the phenotype of macrophages from the M1-like proinflammatory phenotype to M2-like antiinflammatory one contributes to the chronic course of pulmonary TB, dissemination, and persistence of infection. In the present study, we analyzed the features of the expression of CD163, CD204, and CD206 scavenger receptors on macrophages in patients with pulmonary TB. An increase in the number of macrophages carrying markers of the M2 subpopulation (CD163, CD204, and CD206) on their surface was noted, regardless of the clinical form of pulmonary TB and drug resistance of M. tuberculosis.Conclusion. Studying the mechanisms underlying M1 or M2 activation of macrophages is necessary for a deeper understanding of the immunopathogenesis of TB and the role of innate immunity cells in protecting the body from mycobacteria. The analysis of the expression of scavenger receptors CD163, CD204, and CD206 on macrophages allowed to conclude that, in pulmonary TB, especially in patients with drug resistant M. tuberculosis and infiltrative TB, regulatory mechanisms that suppress the activation of innate immunity are implemented together with polarization of macrophage differentiation towards the M2 phenotype. It may be the cause of immune deficiency induced by the pathogen.